Pengaruh Kompensasi dan Kepuasan Kerja Terhadap Kinerja Karyawan PT.Aplikanusa Lintasarta. - Ramadhan, Rezky Akbar; Muhtadin, Imam (Otonomi, 2025)
Abstract The purpose of this study is to look at how compensation and job satisfaction affect employee productivity at PT Aplikanusa Lintasarta. With an associative technique, the study uses a quantitative approach. The Operations Division has 66 workers, and saturated sampling is the sampling method employed. Using hypothesis testing (ttest and Ftest), multiple linear regression, classical assumption tests, and validity and reliability tests, data were obtained via structured questionnaires. The results demonstrate that compensation has a favorable and significant impact on employee performance (t = 2. 289 > ttable = 1. 998; sig. = 0. 025). Additionally, job satisfaction has a positive and substantial influence (t = 4. 874 > ttable = 1. 998; sig. = 0. 000). At the same time, with a coefficient of determination (R²) of 0. 603, compensation and job satisfaction have a significant impact on employee performance (F = 47. 784 > Ftable = 3. 142; sig. = 0. 000). This shows that the two variables account for 60. 3% of an employee's performance, while other factors account for the remaining 39. 7%. The need to implement successful compensation strategies and increase job satisfaction in order to boost employee performance is highlighted by these results. Keywords: Compensation, Job Satisfaction, Employee Performance, Quantitative Analysis